Technological remembering/forgetting: A Faustian bargain?. Issue 2 (8th December 2011) - EEDE, YONI VAN DEN
Ever since computers have been developed, people have dreamt of technological memories. Human memory exhibits crucial limitations with respect to storage capacity, retrievability and transferability - limits that should be overcome by technology. Yet today we are starting to experience the limitations of overcoming these limitations. Pleas are now made to build a certain mode of forgetting into our technologies. As it stands, we are struggling with the tension between technological remembering and forgetting. This article makes an attempt at a deeper philosophical reflection on this tension. First, we sketch a few ideals of technological memory, that have been proposed throughout the last century. Yet lately, different voices have arisen, that point out the dangers and disadvantages of perfect technological remembering. Second, we discuss one of these perspectives and contrast it with the positions in favour of remembering. But this leads us, thirdly, into a discussion on the distinction between technological memory and 'human' memory: these two appear not so easily delineated. How to make sense of, at the same time, the resemblances and the differences between the two? In the ending section, fourthly, we attempt to do so, by way of Marshall McLuhan's theory of technologies as extensions, and Neil Postman's related idea of technology as a 'Faustian bargain'. Technological memory cannot simply imitate human memory, for every technology causes effects we cannot control. But if the 'extending of remembering' makes us eventually regret our greater capabilities and revert to technological forgetting, this 'extending of forgetting' will have its unforeseen consequences as well. In this doubled Faustian bargain, we must ask ourselves towards which of the two sides we have been biased, and how we can reach a balance that combines enforcement with - consciously sought-after - limitations.